Identities of the Kauffman monoid - Chen, Yuzhu; Hu, Xun; Kitov, Nikita V.; Luo, Yanfeng; Volkov, Mikhail V. (Communications in algebra, 2020)
We give a transparent combinatorial characterization of the identities satisfied by the Kauffman monoid Our characterization leads to a polynomial time algorithm to check whether a given identity holds in